Soldiers and Destabilization of Social and Political Situation: World War I Influence on the Revolution Processes in Ukraine (1917) - В. Лозовий (Видавничо-поліграфічний центр "Київський університет", 2014)
The main problem of this paper is to analyze the role play and soldiers in the growth of social extremism in 1917. The author sets the task to highlight the background and development of mass anti-social behavior of soldiers, to find out its mental basis, to reflect the transformation of social psychology soldiers that led to the escalation of revolutionary elements. Found that the actions of the soldiers had rice organizational drawn political and ideological movement. Said motion was mostly criminal anarchist rather than revolutionary political.

Основною проблемою даної статті є відтворення та аналіз ролі солдат у наростанні соціального екстремізму в 1917 році. Автор ставить завдання висвітлити передумови і розвиток масової антисоціальної поведінки солдат, з'ясувати її ментальну основу, відобразити процес трансформації соціальної психології солдат, що призвів до ескалації революційної стихії. З'ясовано, що дії солдатів не мали рис організаційно-оформленого політико-ідеологічного руху. Відтак згаданий рух мав переважно кримінально-анархічний, а не революційно-політичний характер.
Солдати і дестабілізація суспільно-політичного становища: вплив Першої світової війни на революційні процеси в Україні (1917 р.)
Keywords: The First World War; soldiers; Ukrainian revolution; destabilization; Перша світова війна; солдати; Українська революція; дестабілізація